2017
DOI: 10.5812/semj.44979
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Psychiatric Disorders in Iranian Prisoners Based on a Clinical Interview: A Systematic Review and Meta-Analysis

Abstract: Background: Previous reports on the prevalence of mental disorders in Iran indicated a high prevalence of psychotic disorders in both male and female prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
0
19
3
Order By: Relevance
“…In this meta-analysis, the pooled depression prevalence among prisoners in Ethiopia (53.4%) was Larger than an Iranian review and meta-analysis study on 1708 prisoners and 12 articles in which a pooled magnitude of depression was 42% [14] and also another meta-analysis that reported 10% of males and 12% of female worldwide prisoners as having depression [8]. The reason for such a high magnitude in the Ethiopian context would be due to the poor setting of prison and poor health care coverage, poor fulfillment of basic human needs.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this meta-analysis, the pooled depression prevalence among prisoners in Ethiopia (53.4%) was Larger than an Iranian review and meta-analysis study on 1708 prisoners and 12 articles in which a pooled magnitude of depression was 42% [14] and also another meta-analysis that reported 10% of males and 12% of female worldwide prisoners as having depression [8]. The reason for such a high magnitude in the Ethiopian context would be due to the poor setting of prison and poor health care coverage, poor fulfillment of basic human needs.…”
Section: Discussionmentioning
confidence: 56%
“…Depression is prevalent in prisoners [13]. A review and meta-analysis study in Iran on a total of 1708 prisoners and 12 articles obtained a pooled magnitude of depression to be 42%; 44% of male prisoners and 33% of female prisoners [14]. Another meta-analysis reports indicated that 10% of male and 12% of female prisoners [8] and 10.2% of male and 14.1% of female prisoners [8] had depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric disorders are currently widespread across the globe. Anxiety and depression are two highly prevalent disorders in all human societies [1][2][3]. By definition, anxiety is a kind of natural feeling that is experienced in threatening situations.…”
Section: Introductionmentioning
confidence: 99%
“…Common psychiatric and neurodegenerative disorders including anxiety, stress, depression, and insomnia, and the resulting pain have a relatively high prevalence and adversely influence the quality of life [1,3]. These diseases cause anxiety, stress, depression, insomnia and a number of other symptoms.…”
Section: Introductionmentioning
confidence: 99%